ANALISIS RESETTING RELE JARAK AKIBAT UPRATING KONDUKTOR GIS PESANGGARAN - GI SANUR - Rizal Akbar Fauzany; I Gede Dyana Arjana; Cok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2019)
Increased load current on the Pesanggaran – Sanur transmission line by 333,536 Ampere or 83,384 % of the current carrying capacity caused the uprating conductor from ACSR Partridge 135 ????????2 into ACCC Lisbon 310 ????????2. Upratingj cause changes in impendance value. This change affects the zone reach protection of GIS Pesanggaran – GI Sanur distance relay which overlaps with Zone protection of GI Sanur – GI Gianyar distance relay. Resetting is done by recalculation according the distance relay rules and the result are tested with short circuit at 86 % Pesangaran – Sanur transmission line. Resetting result shows the distance relay operate appropriately according with the IEEE Standard C37.113-2015.